Chemiosmotic Energy Conservation in Dinoroseobacter shibae: Proton Translocation Driven by Aerobic Respiration, Denitrification, and Photosynthetic Light Reaction - Kirchhoff, Christian; Ebert, Matthias; Jahn, Dieter; Cypionka, Heribert (Frontiers in Microbiology, 2018)
Dinoroseobacter shibae is an aerobic anoxygenic phototroph and able to utilize light energy to support its aerobic energy metabolism. Since the cells can also grow anaerobically with nitrate and nitrite as terminal electron acceptor, we were interested in how the cells profit from photosynthesis during denitrification and what the steps of chemiosmotic energy conservation are. Therefore, we conducted proton translocation experiments and compared O2-, NO3−- and NO2− respiration during different light regimes and in the dark. We used wild type cells and transposon mutants with knocked-out nitrate- and nitrite reductase genes (napA, nirS), as well as a mutant (ppsR) impaired in bacteriochlorophyll a synthesis. Light had a positive impact on proton translocation, independent of the type of terminal electron acceptor present. In the absence of an electron acceptor, however, light did not stimulate proton translocation. The light-driven add-on to proton translocation was about 1.4 H+/e- for O2 respiration and about 1.1 H+/e- for NO3− and NO2−. We could see that the chemiosmotic energy conservation during aerobic respiration involved proton translocation, mediated by the NADH dehydrogenase, the cytochrome bc1 complex and the cytochrome c oxidase. During denitrification the last proton translocation step of the electron transport was missing, resulting in a lower H+/e- ratio during anoxia. Furthermore, we studied the type of light-harvesting and found that the cells were able to channel light from the green-blue spectrum most efficiently, while red light has only minor impact. This fits well with the depth profiles for D. shibae abundance in the ocean and the penetration depth of light with different wavelenghts into the water column.